Does an Additional Bile Duct Flush With Low-viscosity Preservation Solution Reduce Bile Duct Injury? A Single-blinded Randomized Clinical Trial. Issue 3 (8th February 2023) - Ly, Mark; Lau, Ngee-Soon; McKenzie, Catriona; Kench, James G.; McCaughan, Geoffrey; Crawford, Michael; Pulitano, Carlo
Abstract : Introduction: Biliary complications are a common cause of morbidity after liver transplantation and associated with bile duct injury. To reduce injury, a bile duct flush is performed with high-viscosity preservation solution. It has been suggested that an earlier additional bile duct flush with low-viscosity preservation solution may reduce bile duct injury and biliary complications. This study aimed to investigate whether an earlier additional bile duct flush would reduce bile duct injury or biliary complications. Methods: A randomized trial was conducted using 64 liver grafts from brain dead donors. The control group received a bile duct flush with University of Wisconsin (UW) solution after donor hepatectomy. The intervention group received a bile duct flush using low-viscosity Marshall solution immediately after the onset of cold ischemia and a bile duct flush with University of Wisconsin solution after donor hepatectomy. The primary outcomes were the degree of histological bile duct injury, assessed using the bile duct injury score, and biliary complications within 24 mo of transplant. Results: Bile duct injury scores were not different between the 2 groups. Similar rates of biliary complications occurred in the intervention group (31% [n = 9]) and controls (23% [n = 8]) ( P = 0.573). No difference between groups was observed for anastomotic strictures (24% versus 20%, P = 0.766) or nonanastomotic strictures (7% versus 6%, P = 1.00). Conclusions: This is the first randomized trial to investigate an additional bile duct flush using low-viscosity preservation solution during organ procurement. The findings from this study suggest that performing an earlier additional bile duct flush with Marshall solution does not prevent biliary complications and bile duct injury.